Separation-enrichment-detection integrated aerogel embedded hydrogel material and preparation method thereof

By embedding a hydrogel layer with nano-scale pores in the aerogel SERS chip of cellulose nanofibers and nanometal sols, efficient adsorption enrichment and qualitative detection of organic dyes in wastewater are achieved, and adsorbed materials in the prior art are solved Problems that are susceptible to environmental impacts improve adsorption efficiency and detection accuracy.

CN119114018APending Publication Date: 2024-12-13FUJIAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311713845.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing adsorbent materials are susceptible to extreme acid-base and other pollutants in the treatment of organic dyes in wastewater, resulting in unsatisfactory adsorption effects and the inability to achieve separation, enrichment and detection at the same time.

Method used

Aerogel SERS chip prepared using cellulose nanofibers, sodium alginate and nanometallic sols is embedded in the hydrogel layer of nano-scale pores, and is highly adsorption-enriched by electrostatic and physical adsorption, and the target substance is achieved by SERS detection. qualitative and semi-quantitative detection.

Benefits of technology

It realizes efficient adsorption enrichment and qualitative detection of cationic molecules in wastewater, avoids interference from large particulate matter, improves adsorption efficiency and saturated adsorption amount, and ensures the stability and detection accuracy of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114018A_ABST
    Figure CN119114018A_ABST
Patent Text Reader

Abstract

The invention discloses a separation-enrichment-detection integrated aerogel embedded hydrogel material and a preparation method thereof.The preparation method comprises the steps that firstly, cellulose nanofibers, sodium alginate and nano metal sol serve as raw materials, and a high-specific-surface-area anionic aerogel SERS chip with high adsorbability and an SERS enhancement effect is obtained through freeze drying; the aerogel SERS chip is coated with a cellulose hydrogel layer through freezing embedding, and the cellulose hydrogel layer serves as a filter layer. According to the prepared aerogel embedded hydrogel material, the advantages of aerogel and hydrogel are perfectly combined, and an aerogel SERS chip can efficiently adsorb and enrich cationic molecules in wastewater or other liquid environments through electrostatic interaction, physical adsorption and other processes; nanoscale pores of the hydrogel layer can effectively filter large-particle substances in a matrix environment; and after the aerogel SERS chip enriched with the target substance is taken out, the target substance in the liquid can be qualitatively and semi-quantitatively detected through SERS detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material science and technology, and specifically relates to an aerogel-hydrogel material with integrated "separation-enrichment-detection" functions and a preparation method thereof. Background Art

[0002] Organic dyes are one of the most harmful waterborne pollutants currently, and are widely sourced from many industries, including cosmetics, papermaking, printing, food, textiles, and leather. Due to their high stability and difficulty in biodegradation, organic dyes are difficult to remove from water. Their toxicity, potential mutagenicity, and carcinogenicity pose a significant threat to both the environment and human health. Furthermore, in fields such as biomedicine and food safety, trace amounts of toxic and hazardous substances caused by production residues or illegal additions also pose a potential threat to human health. Extremely low concentrations and complex matrix environments often make the detection of target substances extremely difficult. Therefore, effective separation and enrichment methods are key to their highly sensitive detection. Furthermore, a highly efficient adsorption material is also of great significance in wastewater treatment.

[0003] Currently, a variety of methods have been proposed for treating organic dyes in wastewater, including flocculation, precipitation, membrane separation, and adsorption. Adsorption, however, has gained popularity due to its low cost, ease of operation, and high efficiency, making it one of the most widely used technologies for treating dyes in wastewater. Furthermore, cellulose, due to its high specific surface area and abundant active sites, has been widely used in wastewater adsorption materials.

[0004] The invention patent with publication number CN117019027A discloses a preparation method and application of palm fiber nanocellulose / aramid nanofiber composite aerogel. The prepared composite aerogel has high porosity, uniform and stable adsorption sites, high structural strength, and an adsorption efficiency of more than 92% for cationic dyes. However, the adsorption effect of this aerogel adsorption material that is in direct contact with wastewater is often easily affected by the complex environment in the wastewater. For example, extreme acidity and alkalinity can easily destroy the physical and chemical structure of the aerogel, and some other pollutant components such as fiber fines, sugars, detergents, sulfides, salts, etc. may occupy the adsorption sites, resulting in it not being able to achieve the ideal adsorption effect in actual application.

[0005] Patent publication number CN106362705A discloses a carboxymethylated pulp fiber cationic dye adsorption material, preparation method, and use thereof. This invention utilizes sodium chloroacetate to moderately carboxymethylate pulp fibers, without changing the fibrous morphology of the pulp fibers. The resulting cationic dye adsorption material exhibits high specific surface area, high dispersibility, high selectivity, and high adsorption capacity. The material achieves a maximum removal rate of 96.36% for methyl violet solution. However, this invention shares similar shortcomings to the aforementioned patent publication number CN117019027A: the adsorption material's physicochemical structure is easily damaged in actual wastewater environments, and adsorption sites may become occupied.

[0006] In addition, all the adsorption materials currently disclosed for removing organic dyes from wastewater, including the above invention, only have a simple adsorption effect and cannot achieve the effect of simultaneously detecting the concentration of dyes in wastewater. Summary of the Invention

[0007] To overcome the challenges of the existing technology, the present invention aims to provide an aerogel-hydrogel material with integrated separation-enrichment-detection capabilities and its preparation method. The aerogel SERS "chip" in the aerogel-hydrogel material can efficiently adsorb and enrich cationic molecules in wastewater or other liquid environments through processes such as electrostatic interaction and physical adsorption, while the nanoscale pores of the hydrogel layer effectively filter large particulate matter from the matrix environment. More importantly, after removal, the aerogel SERS "chip" enriched with target substances can be used for qualitative and semi-quantitative detection of target substances in solution through SERS detection.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] An aerogel-hydrogel material with integrated separation-enrichment-detection capabilities, characterized in that the aerogel SERS "chip" in the aerogel-hydrogel material serves as the core and is prepared from cellulose nanofibers, sodium alginate, and nanometal sol;

[0010] The hydrogel layer in the aerogel-embedded hydrogel material serves as a "filter layer" in the adsorption process and is coated on the outside of the aerogel SERS "chip".

[0011] As a possible implementation manner, further, the nano metal particle sol is any one of carboxyl-modified / sulfonated-modified / unmodified nano-gold, nano-silver, nano-core-shell, nano-silicon dioxide, and nano-ferroferric oxide.

[0012] As a possible implementation manner, further, the cellulose nanofibers are selected from any one or more of carboxyl-modified, sulfonated, amino-modified, esterified and unmodified cellulose nanofibers and fiber nanocrystals.

[0013] As a possible implementation, further, the pore size of the aerogel SERS "chip" is 50-500 μm.

[0014] As a possible implementation manner, further, the pore size of the hydrogel shell layer is 5-30 nm.

[0015] As a possible embodiment, further, a method for preparing an aerogel-hydrogel material with integrated "separation-enrichment-detection" function includes the following steps:

[0016] 1) Preparation of aerogel SERS “chip”: CA@Ag NPs

[0017] Preparation of the initial solution of nanosilver sol: Weigh 0.018 g of silver nitrate and add it to 100 mL of deionized water. Heat to a boil at 500 rpm, then add 5 mL of a 1% sodium citrate dihydrate solution. Continue heating and reacting for 1 h. When the color of the solution turns gray-green, the initial solution of nanosilver sol is obtained.

[0018] A cellulose nanofiber solution with a concentration of 0.95% and PL = 10, a sodium alginate solution, and a nanosilver sol concentrate were mixed in proportion, stirred at 30°C and 800 rpm for 30 minutes, and then ultrasonicated at 30°C and 40 kHz for 15 minutes. The mixed solution was then poured into a mold, allowed to stand at 30°C for 20 minutes, and then the mold was frozen flat at -80°C for 30 minutes.

[0019] The mold was then vacuum dried at -80°C for 24 h, and then the mold was removed and the aerogel on it was immersed in a calcium chloride solution for a cross-linking reaction for 1 h.

[0020] The cross-linked aerogel was immersed in ultrapure water and ultrasonicated at 40 kHz for 15 min.

[0021] Next, the aerogel was returned to the mold and frozen flat at -80 °C for 30 min. The mold was then vacuum dried at -80 °C for 24 h and then removed from the mold to obtain CA@Ag NPs.

[0022] 2) Preparation of cellulose solution

[0023] Heat and stir 1-allyl-3-methyl-imidazole-chloride to dissolve it. After it is completely dissolved, slowly add the 1-allyl-3-methyl-imidazole-chloride solution to the bamboo fiber in multiple times, and continue heating and stirring under the original conditions to promote the dissolution of the bamboo fiber.

[0024] When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C and 40 kHz for 20 min to further promote the homogenization of the solution and remove bubbles in the solution.

[0025] 3) Preparation of aerogel-hydrogel material CA@Ag NPs / CH

[0026] A piece of CA@Ag NPs aerogel was taken and saturated with water, and then frozen at -80 °C for 30 min;

[0027] The cellulose solution after ultrasonic degassing was added to the mold, and the frozen CA@Ag NPs aerogel was taken out and quickly immersed in the solution so that the solution completely wrapped the CA@Ag NPs aerogel. The mold was then frozen at -20°C for 1 hour, taken out and allowed to stand at room temperature (25°C) for 12 hours to cross-link the cellulose in the solution. Ultrapure water was then added to the mold to pre-replace the solution and promote its gelation. The gelled sample was then taken out of the mold and immersed in ultrapure water and ultrasonically treated at 30°C and 40 kHz for 30 minutes to completely replace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-chimeric hydrogel SERS substrate material CA@Ag NPs / CH was obtained and stored in ultrapure water for later use.

[0028] As a possible embodiment, further, in step 1), the volume ratio of the cellulose nanofiber solution to the sodium alginate solution is 2:8 to 8:2;

[0029] The volume of the nano-silver sol concentrated solution is 50-100 times the concentration of the initial nano-silver sol solution;

[0030] The volume ratio of the sum of the volumes of the cellulose nanofiber solution and the sodium alginate solution to the nanosilver sol concentrated solution is 1:0.03 to 1:0.08.

[0031] As a possible implementation manner, further, in step 1), the mass fraction of the calcium chloride solution is 0.1-10%.

[0032] As a possible implementation manner, further, in step 2), the stirring speed is 200-800 rpm, the heating temperature is 35-75° C.; and the mass fraction of the obtained bamboo fiber solution is 0.5-3.5%.

[0033] As a possible embodiment, further, in step 3), the volume ratio of CA@Ag NPs to cellulose solution is 1:2 to 1:5 (mm 3 In step 3), the aerogel SERS “chip” is embedded into the hydrogel by the “freeze embedding method”.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1) This invention proposes, for the first time, an aerogel SERS "chip" embedded in a hydrogel, a novel, integrated "separation-enrichment-detection" material. This material seamlessly combines the advantages of both aerogel and hydrogel. The aerogel SERS "chip" efficiently adsorbs and enriches cationic molecules in wastewater or other liquid environments through processes such as electrostatic interaction and physical adsorption. Once the aerogel SERS "chip" has been enriched with target molecules, it can be removed and tested using SERS, enabling qualitative and semi-quantitative detection of target molecules in wastewater.

[0036] 2) The specific pore structure (nano to micron scale) of the hydrogel layer in the present invention can prevent large particles of interfering substances in the sample solution from entering, preventing other substances in the wastewater from occupying the adsorption sites of the aerogel SERS "chip", allowing small molecules to pass through and be captured by the aerogel chip, giving the base material filtration properties, thereby achieving the integration of "separation-enrichment-detection".

[0037] 3) The present invention uses the synergistic effect of hydrogel and aerogel to create a concentration gradient between the hydrogel part and the external solution, greatly improving the saturated adsorption capacity and adsorption efficiency of the aerogel SERS "chip" (the rate at which cationic molecules enter the hydrogel is lower than the adsorption rate of the aerogel chip on the cationic molecules in the hydrogel, so that the concentration of cationic molecules inside the hydrogel is always lower than the concentration of cationic molecules in the external solution, thereby generating a concentration difference). BRIEF DESCRIPTION OF THE DRAWINGS

[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly describes the accompanying drawings required for describing the embodiments. It should be understood that the embodiments described below are only a portion of the embodiments of the present invention, and not all of them. Any other embodiments derived from these embodiments by a person of ordinary skill in the art without inventive effort are also within the scope of protection of the present invention.

[0039] Figure 1 This is a photo of the aerogel SERS “chip” (CA@Ag NPs) prepared in Example 3 of the present invention;

[0040] Figure 2 Surface SEM image of the aerogel SERS “chip” (CA@AgNPs) prepared in Example 3 of the present invention;

[0041] Figure 3Zeta potential diagrams of the sodium alginate solution, nanosilver solution, cellulose nanofiber solution, and a mixed solution of the above three solutions (CA@AgNPs solution) prepared in Example 3 of the present invention;

[0042] Figure 4 The line graph (a) is the SERS detection of the aerogel SERS "chip" (CA@AgNPs) prepared in Example 3 of the present invention (using R6G as the Raman signal molecule) 50 times, and the line graph (b) is the SERS detection of the aerogel SERS "chip" (CA@AgNPs) prepared in Example 3 of the present invention (using R6G as the Raman signal molecule) at 1512 cm -1 The dot diagram (b) is based on the intensity of the characteristic peak at , and the bar diagram (c) is obtained by taking 5 aerogel SERS "chips" (CA@AgNPs) units for SERS detection (5 tests each);

[0043] Figure 5 This is a morphology diagram of the aerogel-embedded hydrogel material (CA@Ag NPs / CH) prepared in Example 3 of the present invention;

[0044] Figure 6 Surface SEM image of the hydrogel "shell" in the aerogel-embedded hydrogel material (CA@Ag NPs / CH) prepared in Example 3 of the present invention;

[0045] Figure 7 This is a test chart of the adsorption of four dyes, R6G, Congo red, crystal violet and methylene blue, to the aerogel chimeric hydrogel material (CA@Ag NPs / CH) prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0047] In the following examples, the method for preparing the initial solution of nanosilver sol is as follows:

[0048] Weigh 0.018g of silver nitrate and add it to 100mL of deionized water. Heat to a boil at 500rpm. Then add 5mL of a 1% sodium citrate dihydrate solution and continue heating for 1 hour. When the solution turns gray-green, the initial nanosilver sol solution is obtained.

[0049] Example 1

[0050] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0051] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 2:8:0.4. The mixture was stirred at 30°C and 800 rpm for 30 minutes, followed by sonication at 30°C and 40 kHz for 15 minutes. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 minutes. The mold was then placed flat in a freezer at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for cross-linking for 1 hour. The cross-linked aerogel was then immersed in a large amount of ultrapure water and sonicated at 40 kHz for 15 minutes. Next, the aerogel was placed back into the mold and placed flat in a -80°C refrigerator for 30 min. The mold was then placed in a freeze dryer and vacuum dried at -80°C for 24 h. The mold was then taken out to obtain CA@Ag NPs.

[0052] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as the cellulose solvent to dissolve bamboo fiber. First, place 1-allyl-3-methyl-imidazole-chloride in a beaker and heat it on a magnetic stirrer at 55°C and 500 rpm to dissolve it. Once completely dissolved, slowly add the 1-allyl-3-methyl-imidazole-chloride solution to the bamboo fiber in multiple portions. Continue heating and stirring under the original conditions to promote dissolution of the bamboo fiber. The amount of bamboo fiber added is 2% by weight of the 1-allyl-3-methyl-imidazole-chloride. Once the bamboo fiber is completely dissolved, ultrasonicate the solution at 40°C and 40 kHz for 20 minutes to further promote homogenization of the solution and remove bubbles in the solution.

[0053] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 750 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0054] Example 2

[0055] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0056] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 4:6:0.4. The mixture was stirred at 30°C and 800 rpm for 30 minutes, followed by sonication at 30°C and 40 kHz for 15 minutes. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 minutes. The mold was then placed flat in a freezer at -80°C for 30 minutes. The mold was then removed and placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for cross-linking for 1 hour. The cross-linked aerogel was then immersed in a large amount of ultrapure water and sonicated at 40 kHz for 15 minutes. Next, the aerogel was placed back into the mold and placed flat in a -80°C refrigerator for 30 min. The mold was then placed in a freeze dryer and vacuum dried at -80°C for 24 h. The mold was then taken out to obtain CA@Ag NPs.

[0057] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as the cellulose solvent to dissolve bamboo fiber. First, place 1-allyl-3-methyl-imidazole-chloride in a beaker and heat it on a magnetic stirrer at 55°C and 500 rpm to dissolve it. Once completely dissolved, slowly add the 1-allyl-3-methyl-imidazole-chloride solution to the bamboo fiber in multiple portions. Continue heating and stirring under the original conditions to promote dissolution of the bamboo fiber. The amount of bamboo fiber added is 2% by weight of the 1-allyl-3-methyl-imidazole-chloride. Once the bamboo fiber is completely dissolved, ultrasonicate the solution at 40°C and 40 kHz for 20 minutes to further promote homogenization of the solution and remove bubbles in the solution.

[0058] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3 The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 750 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0059] Example 3

[0060] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0061] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 6:4:0.4. The mixture was stirred at 30°C, 800 rpm for 30 min, and then ultrasonicated at 30°C, 40 kHz, 80% power (total ultrasonic power 500 W) for 15 min. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 min. The mold was then placed flat in a -80°C freezer and frozen for 30 min. The mold was then removed and placed in a freeze dryer and vacuum-dried at -80°C for 24 h. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for a cross-linking reaction for 1 h. The cross-linked aerogel was immersed in a large amount of ultrapure water and ultrasonically treated at 40 kHz and 80% power (total ultrasonic power 500 W) for 15 minutes. The aerogel was then placed back into the mold and frozen flat again at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed to obtain CA@AgNPs.

[0062] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as a cellulose solvent to dissolve bamboo fiber. First, 1-allyl-3-methyl-imidazole-chloride is placed in a beaker and heated to dissolve on a magnetic stirrer at 55°C and 500 rpm. After complete dissolution, the bamboo fiber is slowly added to the 1-allyl-3-methyl-imidazole-chloride solution in multiple portions. Heating and stirring are continued under the original conditions to promote dissolution of the bamboo fiber. The amount of bamboo fiber added is 2% of the weight of the 1-allyl-3-methyl-imidazole-chloride. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C, 40 kHz, and 80% power (total ultrasonic power of 500 W) for 20 minutes to further promote homogenization of the solution and remove bubbles in the solution.

[0063] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 750 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0064] Example 4

[0065] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0066] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 8:2:0.4. The mixture was stirred at 30°C, 800 rpm for 30 minutes, and then ultrasonicated at 30°C, 40 kHz, 80% power (total ultrasonic power 500 W) for 15 minutes. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 minutes. The mold was then placed flat in a -80°C freezer and frozen for 30 minutes. The mold was then removed and placed in a freeze dryer for vacuum drying at -80°C for 24 hours. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for a cross-linking reaction for 1 hour. The cross-linked aerogel was immersed in a large amount of ultrapure water and ultrasonically treated at 40 kHz and 80% power (total ultrasonic power 500 W) for 15 minutes. The aerogel was then placed back into the mold and frozen flat again at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed to obtain CA@AgNPs.

[0067] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as a cellulose solvent to dissolve bamboo fiber. First, 1-allyl-3-methyl-imidazole-chloride is placed in a beaker and heated to dissolve on a magnetic stirrer at 55°C and 500 rpm. After complete dissolution, the bamboo fiber is slowly added to the 1-allyl-3-methyl-imidazole-chloride solution in multiple portions. Heating and stirring are continued under the original conditions to promote dissolution of the bamboo fiber. The amount of bamboo fiber added is 2% of the weight of the 1-allyl-3-methyl-imidazole-chloride. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C, 40 kHz, and 80% power (total ultrasonic power of 500 W) for 20 minutes to further promote homogenization of the solution and remove bubbles in the solution.

[0068] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3 The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 750 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0069] Example 5

[0070] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0071] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 6:4:0.4. The mixture was stirred at 30°C, 800 rpm for 30 min, and then ultrasonicated at 30°C, 40 kHz, 80% power (total ultrasonic power 500 W) for 15 min. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 min. The mold was then placed flat in a -80°C freezer and frozen for 30 min. The mold was then removed and placed in a freeze dryer and vacuum-dried at -80°C for 24 h. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for a cross-linking reaction for 1 h. The cross-linked aerogel was immersed in a large amount of ultrapure water and ultrasonically treated at 40 kHz and 80% power (total ultrasonic power 500 W) for 15 minutes. The aerogel was then placed back into the mold and frozen flat again at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed to obtain CA@AgNPs.

[0072] S2, preparation of cellulose dissolution solution: 1-allyl-3-methyl-imidazole-chloride is used as a cellulose solvent to dissolve bamboo fiber. First, 1-allyl-3-methyl-imidazole-chloride is placed in a beaker and heated to dissolve on a magnetic stirrer at 55°C and 500rpm. After complete dissolution, the bamboo fiber is slowly added to the 1-allyl-3-methyl-imidazole-chloride solution in multiple portions. Heating and stirring are continued under the original conditions to promote the dissolution of the bamboo fiber. The amount of bamboo fiber added is 2.5% of the mass of 1-allyl-3-methyl-imidazole-chloride. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C, 40KHz, 80% power (total ultrasonic power 500W) for 20 minutes to further promote the homogenization of the solution and remove bubbles in the solution.

[0073] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 750 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0074] Example 6

[0075] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0076] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 6:4:0.4. The mixture was stirred at 30°C, 800 rpm for 30 min, and then ultrasonicated at 30°C, 40 kHz, 80% power (total ultrasonic power 500 W) for 15 min. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 min. The mold was then placed flat in a -80°C freezer and frozen for 30 min. The mold was then removed and placed in a freeze dryer and vacuum-dried at -80°C for 24 h. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for a cross-linking reaction for 1 h. The cross-linked aerogel was immersed in a large amount of ultrapure water and ultrasonically treated at 40 kHz and 80% power (total ultrasonic power 500 W) for 15 minutes. The aerogel was then placed back into the mold and frozen flat again at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed to obtain CA@AgNPs.

[0077] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as a cellulose solvent to dissolve bamboo fiber. First, 1-allyl-3-methyl-imidazole-chloride is placed in a beaker and heated to dissolve on a magnetic stirrer at 55°C and 500 rpm. After complete dissolution, the bamboo fiber is slowly added to the 1-allyl-3-methyl-imidazole-chloride solution in multiple portions. Heating and stirring are continued under the original conditions to promote the dissolution of the bamboo fiber. The amount of bamboo fiber added is 3% of the mass of 1-allyl-3-methyl-imidazole-chloride. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C, 40 kHz, and 80% power (total ultrasonic power of 500 W) for 20 minutes to further promote the homogenization of the solution and remove bubbles in the solution.

[0078] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3 The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 750 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0079] Example 7

[0080] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0081] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 6:4:0.4. The mixture was stirred at 30°C, 800 rpm for 30 min, and then ultrasonicated at 30°C, 40 kHz, 80% power (total ultrasonic power 500 W) for 15 min. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 min. The mold was then placed flat in a -80°C freezer and frozen for 30 min. The mold was then removed and placed in a freeze dryer and vacuum-dried at -80°C for 24 h. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for a cross-linking reaction for 1 h. The cross-linked aerogel was immersed in a large amount of ultrapure water and ultrasonically treated at 40 kHz and 80% power (total ultrasonic power 500 W) for 15 minutes. The aerogel was then placed back into the mold and frozen flat again at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed to obtain CA@AgNPs.

[0082] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as a cellulose solvent to dissolve bamboo fiber. First, 1-allyl-3-methyl-imidazole-chloride is placed in a beaker and heated to dissolve on a magnetic stirrer at 55°C and 500 rpm. After complete dissolution, the bamboo fiber is slowly added to the 1-allyl-3-methyl-imidazole-chloride solution in multiple portions. Heating and stirring are continued under the original conditions to promote dissolution of the bamboo fiber. The amount of bamboo fiber added is 2% of the weight of the 1-allyl-3-methyl-imidazole-chloride. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C, 40 kHz, and 80% power (total ultrasonic power of 500 W) for 20 minutes to further promote homogenization of the solution and remove bubbles in the solution.

[0083] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 850 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0084] Example 8

[0085] The preparation method of the aerogel-hydrogel material with integrated “separation-enrichment-detection” in this embodiment specifically includes the following steps:

[0086] S1. Preparation of aerogel SERS "chip" (CA@Ag NPs): A cellulose nanofiber solution (0.95%) with a PL of 10 (0.95%), a sodium alginate solution (1.5%), and a concentrated silver nanoparticle sol solution (50 times the initial silver nanoparticle sol concentration) were mixed in a volume ratio of 6:4:0.4. The mixture was stirred at 30°C, 800 rpm for 30 min, and then ultrasonicated at 30°C, 40 kHz, 80% power (total ultrasonic power 500 W) for 15 min. The mixed solution was then poured into a polytetrafluoroethylene mold and allowed to stand at 30°C for 20 min. The mold was then placed flat in a -80°C freezer and frozen for 30 min. The mold was then removed and placed in a freeze dryer and vacuum-dried at -80°C for 24 h. The mold was then removed and the aerogel was immersed in a 0.3% calcium chloride solution for a cross-linking reaction for 1 h. The cross-linked aerogel was immersed in a large amount of ultrapure water and ultrasonically treated at 40 kHz and 80% power (total ultrasonic power 500 W) for 15 minutes. The aerogel was then placed back into the mold and frozen flat again at -80°C for 30 minutes. The mold was then placed in a freeze dryer and vacuum-dried at -80°C for 24 hours. The mold was then removed to obtain CA@AgNPs.

[0087] S2. Preparation of cellulose solution: 1-allyl-3-methyl-imidazole-chloride is used as a cellulose solvent to dissolve bamboo fiber. First, 1-allyl-3-methyl-imidazole-chloride is placed in a beaker and heated to dissolve on a magnetic stirrer at 55°C and 500 rpm. After complete dissolution, the bamboo fiber is slowly added to the 1-allyl-3-methyl-imidazole-chloride solution in multiple portions. Heating and stirring are continued under the original conditions to promote dissolution of the bamboo fiber. The amount of bamboo fiber added is 2% of the weight of the 1-allyl-3-methyl-imidazole-chloride. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C, 40 kHz, and 80% power (total ultrasonic power of 500 W) for 20 minutes to further promote homogenization of the solution and remove bubbles in the solution.

[0088] S3. Preparation of aerogel-hydrogel material (CA@Ag NPs / CH): Take a 10×10×3mm 3 The CA@AgNPs aerogel was saturated with water and then placed in a -80°C freezer for 30 minutes. The degassed solution was added to a mold. The frozen CA@AgNPs aerogel was removed and quickly immersed in 950 μL of cellulose solution, allowing the solution to completely encapsulate the CA@AgNPs aerogel. The mold was then quickly placed in a -20°C freezer for 1 hour. Afterwards, the mold was removed and allowed to stand at room temperature (25°C) for 12 hours to allow the cellulose in the solution to crosslink. Ultrapure water was then added to the mold to pre-displace the solution and induce gelation. The gelled sample was removed from the mold and immersed in a large amount of ultrapure water. Ultrasonic treatment was then performed at 30°C, 40 kHz for 30 minutes to completely displace the 1-allyl-3-methyl-imidazole-chloride in the sample. Finally, the aerogel-hydrogel SERS substrate, CA@AgNPs / CH, was obtained and stored in ultrapure water until further use.

[0089] Refer to the attached Figure 1 As shown in the figure, it can be seen that the aerogel SERS "chip" (CA@AgNPs) prepared in this Example 3 has a three-dimensional porous structure.

[0090] Refer to the attached Figure 2 As shown in the figure, it can be seen that there is an obvious three-dimensional porous structure in CA@AgNPs, and the pore size is 50μm-500μm.

[0091] Refer to the attached Figure 3 As shown in the figure, it can be seen that the three raw materials used to prepare CA@Ag NPs: sodium alginate, cellulose nanofibers and nanosilver sol all have negative charges; therefore, their mixed solution (CA@Ag NPs solution) shows a strong negative charge (~50mV), which means that the prepared aerogel SERS "chip" (CA@AgNPs) can produce strong electrostatic interactions with cationic molecules during the adsorption process.

[0092] Refer to the attached Figure 4 As shown, combined Figure 4 As can be seen from the two figures (a) and (b) and RSD = 4.47%, the aerogel SERS "chip" (CA@AgNPs) has excellent SERS test uniformity; combined with Figure 4 (c) and RSD = 1.87%, it can be seen that the aerogel SERS "chip" (CA@AgNPs) has good reproducibility.

[0093] Refer to the attached Figure 5 As shown in the figure, it can be seen that the aerogel SERS "chip" (CA@AgNPs) is completely wrapped by the hydrogel "shell".

[0094] Refer to the attached Figure 6 As shown in the figure, it can be seen that the hydrogel "shell" has a smooth surface and fine and uniform gaps, the width of which is 5nm-30nm, which means that during the adsorption process, the hydrogel "shell" can effectively isolate large particles in the matrix environment.

[0095] Refer to the attached Figure 7 As shown in the figure, it can be seen that after adsorption, the colors of the four dye solutions become obviously lighter.

[0096] Through Figure 7 The experimental results were calculated and the concentrations of the four dye solutions after adsorption were 13.60%, 14.53%, 17.06%, and 23.39% of the initial solution concentration, respectively, as shown in Table 1. This means that CA@Ag NPs / CH has a good adsorption effect on cationic molecules.

[0097] Table 1

[0098]

[0099] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. An aerogel-hydrogel material with integrated "separation-enrichment-detection" function, characterized in that: The aerogel SERS "chip" in the aerogel-embedded hydrogel material is used as the core and is prepared from cellulose nanofibers, sodium alginate and nano-metal sol; The hydrogel layer in the aerogel-embedded hydrogel material serves as a "filter layer" in the adsorption process and is coated outside the aerogel SERS "chip".

2. The aerogel-hydrogel material with integrated “separation-enrichment-detection” according to claim 1, characterized in that: The nano metal particle sol is any one of carboxyl modified / sulfonated modified / unmodified nano gold, nano silver, nano core-shell, nano silicon dioxide, and nano ferroferric oxide.

3. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 1, characterized in that: The cellulose nanofibers are selected from any one or more of carboxyl-modified, sulfonated, amino-modified, esterified-modified and unmodified cellulose nanofibers and fiber nanocrystals.

4. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 2, characterized in that: The pore size of the aerogel SERS "chip" is 50-500 μm.

5. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 3, characterized in that: The pore size of the hydrogel shell layer is 5-30 nm.

6. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 1, characterized in that: The preparation method thereof comprises the following steps: 1) Preparation of aerogel SERS "chip": CA@Ag NPs Preparation of initial solution of nano-silver sol: weigh 0.018g of silver nitrate and add it to 100mL of deionized water, heat and boil at 500rpm, then add 5mL of 1% sodium citrate dihydrate solution, continue heating and reacting for 1h, and when the color of the solution turns gray-green, the initial solution of nano-silver sol is obtained; A cellulose nanofiber solution with a concentration of 0.95% and PL=10, a sodium alginate solution and a nanosilver sol concentrate were mixed in proportion, stirred at 30°C and 800 rpm for 30 min, and then ultrasonicated at 30°C and 40 kHz for 15 min. The mixed solution was then poured into a mold, allowed to stand at 30°C for 20 min, and then the mold was laid flat and frozen at -80°C for 30 min. The mold was then vacuum dried at -80 °C for 24 h, and then the mold was taken out and the aerogel on it was immersed in a calcium chloride solution for a cross-linking reaction for 1 h; The cross-linked aerogel was immersed in ultrapure water and ultrasonicated at 40 KHz for 15 min; Next, the aerogel was put back into the mold and frozen flat at -80 °C for 30 min again. The mold was then vacuum dried at -80 °C for 24 h and then taken out to obtain CA@Ag NPs. 2) Preparation of cellulose solution Heat and stir 1-allyl-3-methyl-imidazole-chloride to dissolve. After it is completely dissolved, slowly add the bamboo fiber into the 1-allyl-3-methyl-imidazole-chloride solution in multiple times, and continue heating and stirring under the original conditions to promote the dissolution of the bamboo fiber. When the bamboo fiber is completely dissolved, the solution is ultrasonicated at 40°C and 40KHz for 20 minutes. 3) Preparation of aerogel-hydrogel material CA@Ag NPs / CH A piece of CA@Ag NPs aerogel was taken to make it saturated with water and then frozen at -80 °C for 30 min; The cellulose solution after ultrasonic degassing was added to the mold, and the frozen CA@Ag NPs aerogel was taken out and quickly immersed in the solution so that the solution completely wrapped the CA@Ag NPs aerogel. The mold was then frozen at -20°C for 1 hour. The mold was taken out and allowed to stand at room temperature for 12 hours, and ultrapure water was added to the mold. The gelled sample was then taken out of the mold and immersed in ultrapure water, and ultrasonically treated at 30°C and 40KHz for 30 minutes to obtain the aerogel chimeric hydrogel SERS substrate material CA@AgNPs / CH.

7. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 6, characterized in that: In step 1), the mass fraction of the sodium alginate solution is 0.5%-3%; The volume of the nano silver sol concentrated solution is 50-100 times the concentration of the nano silver sol initial solution; The volume ratio of the sum of the volumes of the cellulose nanofiber solution and the sodium alginate solution to the nanosilver sol concentrated solution is 1:0.03 to 1:0.

08.

8. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 6, characterized in that: The mass fraction of the calcium chloride solution in step 1) is 0.1-10%.

9. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 6, characterized in that: In step 2), the stirring speed is 200-800 rpm, and the heating temperature is 35-75° C.; the mass fraction of the obtained bamboo fiber solution is 0.5-3.5%.

10. The aerogel-hydrogel material with "separation-enrichment-detection" integration according to claim 6, characterized in that: In step 3), the volume ratio of CA@Ag NPs to cellulose solution is 1:2 to 1:5 (mm 3 / μL).

Citation Information

Patent Citations

  • Carboxymethyl cationic dye adsorption material prepared from paper pulp fiber, preparation method and application

    CN106362705A

  • Preparation method and application of palm fiber nanocellulose / aramid nanofiber composite aerogel

    CN117019027A